The secret life of degradative lysosomes in axons: delivery from the soma, enzymatic activity, and local autophagic clearance. Issue 1 (2nd January 2020) - Farfel-Becker, Tamar; Roney, Joseph C.; Cheng, Xiu-Tang; Li, Sunan; Cuddy, Sean R.; Sheng, Zu-Hang
ABSTRACT: Lysosomal degradation of protein aggregates and damaged organelles is essential for maintaining cellular homeostasis. This process in neurons is challenging due to their highly polarized architecture. While enzymatically active degradative lysosomes are enriched in the cell body, their trafficking and degradation capacity in axons remain elusive. We recently characterized the axonal delivery of degradative lysosomes by applying a set of fluorescent probes that selectively label active forms of lysosomal hydrolases on cortical neurons in microfluidic devices. We revealed that soma-derived degradative lysosomes rapidly influx into distal axons and target to autophagosomes and Parkinson disease-related SNCA/α-synuclein cargos for local degradation. Disrupting axon-targeted delivery of degradative lysosomes induces axonal autophagic stress. We demonstrate that the axon is an active compartment for local degradation, establishing a foundation for future investigations into axonal lysosome trafficking and functionality in neurodegenerative diseases and lysosomal storage disorders associated with axonal pathology and macroautophagy/autophagy stress.